On the orbit of an A-m-isometry - Rabaoui, Rchid; Saddi, Adel (Annales Mathematicae Silesianae, 2013)
An A-m-isometry is a bounded linear operator T on a Hilbert space ℍ satisfying an identity of the form Σk=0m(-1)m-kmkT*kATk = 0, where A is a positive (semi-definite) operator. In this paper, we show that the results for the supercyclicity and the hypercyclicity of m-isometries described in [6, 8] remain true for A-m-isometries.